Modern Psychology and Ancient Wisdom : Psychological Healing Practices from the World's Religious Traditions. - Mijares, Sharon G. (Taylor and Francis, 2014)
Harness the psychospiritual healing potential of prayer, meditation, breathing, and more!This thoughtful anthology illuminates ancient ways of psychospiritual healing. Research has shown the healing potential of prayer, meditation, controlled breathing, and other timeless spiritual disciplines. This extraordinary book brings together experts who explore these concepts from the perspectives of Christianity, Buddhism, Sufism, the Goddess tradition, Judaism, Native American spirituality, Taoism, and Hinduism/Yoga. In Modern Psychology and Ancient Wisdom: Psychological Healing.